Anti-inflammatory compound curcumin and mesenchymal stem cells in the treatment of spinal cord injury in rats - Ruzicka, Jiri; Machová Urdzíková, Lucia; Kloudova, Anna; Amin, Anubhav G; Vallova, Jana; Kubinova, Sarka; Schmidt, Meic H; Jhanwar-Uniyal, Meena; Jendelova, Pavla (Acta Neurobiologiae Experimentalis, 2018)
Spinal cord injury leads to a robust inflammatory response that is an unfavorable environment for stem cell implantation. In this study, we evaluated the effect of combined therapy of curcumin and mesenchymal stem cells (MSC) on behavioral recovery and tissue sparing, glial scar formation, axonal sprouting and inflammatory responses in a rat experimental model of spinal cord injury (SCI). Balloon-induced compression lesion was performed at thoracic (Th8-9) spinal level. Out of the four groups studied, two groups received curcumin on the surface of the spinal cord immediately after SCI and then once a week for 3 weeks together with an intraperitoneal daily curcumin injection for 28 days. The other two groups received saline. Seven days after SCI, human MSC were intrathecally implanted in one curcumin and one saline group. Both curcumin and curcumin combined with MSC treatment improved locomotor ability in comparison to the saline treated animals. The combined treatment group showed additional improvement in advanced locomotor performance. The combined therapy facilitated axonal sprouting, and modulated expression of pro-regenerative factors and inflammatory responses, when compared to saline and single treatments. These results demonstrate that preconditioning with curcumin, prior to the MSC implantation could have a synergic effect in the treatment of experimental SCI.
Keywords: antiflogistika; poranění míchy; Mesenchymal Stem Cell Transplantation; Spinal Cord Injuries; obnova funkce; zvířata; Nerve Regeneration; kurkumin; regenerace nervu; potkani Wistar; Curcumin; transplantace mezenchymálních kmenových buněk; Rats, Wistar; mezenchymální kmenové buňky; Recovery of Function; Anti-Inflammatory Agents; Animals; Disease Models, Animal; Mesenchymal Stem Cells; modely nemocí na zvířatech